If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(-10 + -2x) = -84 (-10 * -7 + -2x * -7) = -84 (70 + 14x) = -84 Solving 70 + 14x = -84 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + 14x = -84 + -70 Combine like terms: 70 + -70 = 0 0 + 14x = -84 + -70 14x = -84 + -70 Combine like terms: -84 + -70 = -154 14x = -154 Divide each side by '14'. x = -11 Simplifying x = -11
| -12+4v=8 | | -2/5x=-3/4 | | 2(3p+5)+p=13-2p+15 | | 4/18*8 | | -8+3x+6x=1 | | -3d+5d+10=0 | | 7x-9=4c | | Y+10=x | | -8=-4/9x | | 14-3n=-22 | | 7/2x+1/2x=4x+9/2+9/2x | | 5(4x+1)-12x=2(4x-2) | | 4(2x+3)=-44 | | (x+3)*3=(x-23)*7 | | 3y-3+y+17=7y+20-5y | | x-9=-7+3 | | 8/36(4/4) | | 7+14x-2=9x+17-7x | | -8=4/9x | | 3-x+6x=-12 | | 6(x-0.8)-0.2(5x-4)=2 | | 16/51x3/10 | | 2T=5P/S | | c=38.22+0.25 | | 3p-2q=7 | | 2(y-4)=-4(y+8) | | -5x-9x=98 | | 1.4-.04x=5.20 | | -2u/5=-10 | | 44-6x=3x+23 | | 25=3+3n-5 | | 9x+12=-177 |